Teori Epistemologi Islam; Telaah Kritis Pemikiran Mulyadhi Kartanegara - Deden Ridwan (Budapest International Research and Critics University, 2018)
Mystic-philosophical, according to Mulyadi Kartanegara, is a space where there is a struggle between the senses, the mind and the heart which are interrelated to provide knowledge about humans. These three icons then form the foundation of Islamic epistemology, in this case mystico-philosophical. However, these three things have been said to have not yet run out in love in reconciling science between religion and philosophy, science and religion, religion and other scientific disciplines, even creating sharp abyss. Over the course of the history of thought, the gulf continues to be pursued to be synergized in unity and to eliminate the gulf, according to Mulyadhi Kartanegara, is mystico-philosophical.